Relationships among atmosphere-cryosphere-biosphere in a transitional glacial catchment (Sabbione Lake, North-Western Italian Alps) - COLOMBO, NICOLA; FRATIANNI, SIMONA; Giaccone E.; Paro L. (Naaim-Bouvet F., Durand Y., Lambert R., Létang D., Rapin F., 2013)
The present study has been carried out in the Sabbione Basin (North Western Italian Alps, Ossola Valley). In this area there is a storage pond (1.226 km2) which gathers the ablation waters of the glaciers situated within the site; the main glaciers are the Northern Sabbione Glacier (ca. 1.25 km2) and the Southern Sabbione Glacier (ca. 2.50 km2). Climatological, geomorphological and vegetational studies have been conducted in order to understand the connections between climate change and its possible effects on cryosphere, geosphere and biosphere. We have analysed air temperature, liquid and solid (fresh snow) precipitation recorded in the meteorological stations of Formazza – Pian dei Camosci (2,453 m above sea level, from 1988 to 2012) and Sabbione (2,470 m above sea level, from 1950 to 2012), located within the study area. The results have been related to the previous studies available for the Ossola Valley in order to better investigate the trends of the main climatic parameters in the context of climate change, with particular attention to the amount of snowfall, thickness and persistence of snow cover. In addition, we have analysed some stratigraphic profiles of snow cover (AINEVA) and snow density data recorded in the automatic/manned meteorological stations of Meteomont Service (Corpo Forestale dello Stato and Comando Truppe Alpine) for the characterization of the snowpack. A detailed geomorphological map (scale 1:10000) has been created from the aerial photographic interpretation of multitemporal images and digital orthoimages (from 1955 to 2010). Moreover, field surveys have been conducted (during the summer 2012) with the aim to identify micromorphological forms resulting from cryotic remodelling processes on deposits (eg. patterned ground, cryoturbation, etc.). Vegetational samples on grassland and debris deposits have been taken with the phytosociological method, in order to characterize the main habitats to produce a preliminary map of vegetation. To determine the presence/absence of permafrost the ...